2021
DOI: 10.9734/jpri/2021/v33i50a33385
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Screening through Molecular Docking Analysis to Identify Potential Natural Inhibitor(s) of Lyn Tyrosine Kinase- An In-silico Approach

Abstract: Breast cancer on becoming one of the leading cancer types, emerged as an important barrier in increasing life expectancy of the overall population. In the current study, some compounds were screened based on literature survey for the identification of natural bioactive compounds as potential inhibitors of Lyn tyrosine kinase. Therefore, a multi-step molecular docking was carried out using AutoDock embedded in the MGL Tools. After initial screening, molecules having a higher docking score and binding free energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…Recent studies have shown the relationship between baicalein and immune cells to counteract fibrosis, such as the downregulation of expression of proinflammatory cytokines and chemokines (e.g., interleukin (IL)-1β, IL-6, tumor necrosis factor-alpha (TNF-α) and monocyte chemoattractant protein-1 (MCP-1)) [ 13 ] and inhibition of infiltration of inflammatory cells (macrophages and lymphocytes) [ 26 ]. Baicalein has been identified as an inhibitor of Lyn kinase [ 27 ], which is the first signal-transducing kinase required for B cell activation in SSc patients [ 28 ] and contributes to the development of systemic autoimmunity and skin sclerosis through CD19-dependent pathway in tight skin mice [ 29 ]. Moreover, spleen tyrosine kinase (Syk) is another tyrosine kinase after B cell receptor (BCR) activation which is involved in the sclerodermatous process via B cell signaling [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown the relationship between baicalein and immune cells to counteract fibrosis, such as the downregulation of expression of proinflammatory cytokines and chemokines (e.g., interleukin (IL)-1β, IL-6, tumor necrosis factor-alpha (TNF-α) and monocyte chemoattractant protein-1 (MCP-1)) [ 13 ] and inhibition of infiltration of inflammatory cells (macrophages and lymphocytes) [ 26 ]. Baicalein has been identified as an inhibitor of Lyn kinase [ 27 ], which is the first signal-transducing kinase required for B cell activation in SSc patients [ 28 ] and contributes to the development of systemic autoimmunity and skin sclerosis through CD19-dependent pathway in tight skin mice [ 29 ]. Moreover, spleen tyrosine kinase (Syk) is another tyrosine kinase after B cell receptor (BCR) activation which is involved in the sclerodermatous process via B cell signaling [ 30 ].…”
Section: Introductionmentioning
confidence: 99%